The impact of behavioral economics on investment decisions - Özkoçak, Gamze (My University, 2019)
In recent years, Behavioral Finance Theory has been developed in order to show that people have different characteristics than it is assumed and that the behaviors of investors can differ from each other because each individual does not have the same rational behaviors. According to the Theory of Behavioral Finance, people do not act rationally and cannot always make optimum decisions. People can make different decisions and make mistakes under various factors such as their moods, psychologies and living conditions, and with this situation, they can cause falls or increases from time to time to different movements in the markets. One of the most important differences in human characteristics is the personality, so it is concluded that the personality traits can have an effect on the decisions taken in the behavioral finance. In this study, it is aimed to reveal the behavioral finance dimension of investment decisions in insurance sector employees. The sample of the study consisted of 384 participants working in various insurance companies in Istanbul. In order to collect the research data, personal information form and investment information, along with the Temperament and Character Characteristics Scale and Investment Decisions Scale were used. The data were analyzed with descriptive statistics, correlation, regression, t-test and ANOVA analysis at SPSS 23.00. The findings were evaluated at 95% confidence interval and 5% significance level. The findings of the study reveal that the investment decisions of the participants differ according to their demographic characteristics and investment preferences.

Son yıllarda insanların varsayılandan daha farklı özellikler taşıması ve her bireyin birbirinin aynısı olan rasyonel davranışlara sahip olmaması sebebiyle yatırımcı davranışlarının birbirinden farklılık gösterebileceği ortaya koyularak Davranışsal Finans Teorisi geliştirilmiştir. Davranışsal Finans Teorisi’ne göre insanlar rasyonel davranmamakta ve her zaman optimum kararlar verememektedir. İnsanlar kendi ruh halleri, psikolojileri, yaşam koşulları gibi birçok etkenin altında birbirlerinden farklı kararlar verebilmekte, hatalar yapabilmekte ve bu durumla birlikte de piyasalarda farklı hareketlenmelere zaman zaman düşüş veya yükselişlere sebep olabilmektedirler. İnsan üzerinde en önemli farklılık gösteren özelliklerden birisi de kişilik olması sebebiyle, her birey bir diğerinden farklı bir kişilik özelliği taşıdığı düşünülürse, kişilik özelliklerinin de davranışsal finansta alınan kararlar üzerinde etkili olabildiği sonucuna varılmaktadır. Bu noktadan hareketle hazırlanan araştırmada sigorta sektörü çalışanlarında yatırım kararlarının davranışsal finans boyutunun ortaya çıkarılması amaçlanmıştır. Araştırmanın örneklemini İstanbul’da çeşitli sigorta işletmelerinde çalışan 384 katılımcı oluşturmaktadır. Araştırma verilerinin toplanmasında kişisel bilgi formu ve yatırım bilgileri ile birlikte Yatırım Kararları Ölçeği kullanılmıştır. Verilerin analizi SPSS 23.00’da betimleyici istatistikler, t-test ve ANOVA analizleri ile gerçekleştirilmiştir. Elde edilen bulgular %95 güven aralığında ve %5 anlamlılık düzeyinde değerlendirilmiştir. Araştırmadan elde edilen bulgular, katılımcıların yatırım kararlarının, demografik özellikleri ile yatırım tercihlerine göre farklılaştığını ortaya koymaktadır.
Tez (Yüksek Lisans) - Yıldız Teknik Üniversitesi, Sosyal Bilimler Enstitüsü, 2019
Keywords: Behavioral finance; Investor psychology; Investment; Decision making; Davranışsal finans; Yatırımcı psikolojisi; Yatırım; Karar verme